Suppressive regulatory T cells and latent transforming growth factor-β-expressing macrophages are altered in the peritoneal fluid of patients with endometriosis - Tetsuro Hanada; Shunichiro Tsuji; Misako Nakayama; Shiro Wakinoue; Kyoko Kasahara; Fuminori Kimura; Takahide Mori; Kazumasa Ogasawara; Takashi Murakami (BMC, 2018)
Abstract Background Endometriosis is a known cause of infertility. Differences in immune tolerance caused by regulatory T cells (Tregs) and transforming growth factor-β (TGF-β) are thought to be involved in the pathology of endometriosis. Evidence has indicated that Tregs can be separated into three functionally and phenotypically distinct subpopulations and that activated TGF-β is released from latency-associated peptide (LAP) on the surfaces of specific cells. The aim of this study was to examine differences in Treg subpopulations and LAP in the peripheral blood (PB) and peritoneal fluid (PF) of patients with and without endometriosis. Methods PB and PF were collected from 28 women with laparoscopically and histopathologically diagnosed endometriosis and 20 disease-free women who were subjected to laparoscopic surgery. Three subpopulations of CD4+ T lymphocytes (CD45RA+FoxP3low resting Tregs, CD45RA−FoxP3high effector Tregs, and CD45RA−FoxP3low non-Tregs) and CD11b+ mononuclear cells expressing LAP were analyzed by flow cytometry using specific monoclonal antibodies. Results Proportions of suppressive Tregs (resting and effector Tregs) were significantly higher in the PF samples of patients with endometriosis than in those of control women (P = 0.02 and P < 0.01, respectively) but did not differ between the PB samples of patients and controls. The percentage of CD11b+LAP+ macrophages was significantly lower in PF samples of patients with endometriosis than in those of controls (P < 0.01) but was not altered in the PB samples. Conclusion Proportions of suppressive Tregs and LAP+ macrophages are altered locally in the PF of endometriosis patients.